The use of otolith to determine age and spawning time of red devil Amphilophus labiatus [Gunther, 1864] in Sermo Reservoir, Yogyakarta - Sitty Ainsyah Habibie; Djumanto Djumanto; Rustadi Rustadi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2015)
The purpose of this study was to determine the age and spawning time of red devil (Amphilophus labiatus) based on the observation of the daily increment of otolith in juvenile fish. The sampling was conducted from October 2013 to March 2014. The juveniles were collected biweekly using a hapa net and scoop net. To determine the first formation of daily increment, the brood stock of tilapia (Oreochromis sp.) was spawned in captivity. A total of five larvae was taken every day from hatching day until the 18 days old, and then the larvae were taken every two days. Sagittal otoliths were collected by putting the larva into a 5.25% NaOCl solution. The left otolith was attached to the object glass using Bucherer cement, and then dropped with Canada balsam and closed by cover glass. The numbers of daily increment were observed by using a microscope with a magnification 100-400 X. The age was determined based on the number of daily increment plus the first time of ring formation. Spawning time was determined by back calculation of the sampling time, plus age and incubation period. The result showed that there were 130 individual juveniles collected ranged from 7.0 to 14.6 mm total length (TL). The formation of daily increment on 69 sagittal otolits was observed. The first sagittal increment was formed on the third day after hatching and the forming of the increment was daily. The ages of juvenile red devil were between 9-28 days old and majority of the larvae in 17 days. Red devil spawned coincided with the new moon phase and high intensity of rainfalls. Abstrak Penelitian ini bertujuan untuk menentukan umur dan waktu pemijahan ikan red devil berdasarkan jumlah lingkaran ha-rian pada otolit juwana ikan. Penelitian dilakukan dari bulan Oktober 2013 hingga Maret 2014. Pengambilan contoh ikan dilakukan tiap dua mingguan dengan menggunakan waring dan seser. Guna menentukan awal pembentukan ling-karan harian pada otolit, maka dilakukan pengamatan terhadap otolit larva ikan nila albino (Oreochromis sp.) hasil te-tasan. Sebanyak lima ekor larva diambil tiap hari sejak menetas hingga umur 18 hari, selanjutnya larva diambil tiap dua hari. Otolit sagitta diambil dengan cara merendam ikan menggunakan larutan NaOCl 5,25%. Otolit yang tertinggal se-lanjutnya direkatkan pada objek gelas menggunakan semen bucherer, dan ditutup menggunakan kanada balsam serta kaca penutup. Pengamatan jumlah lingkaran harian menggunakan mikroskop dengan pembesaran 100-400 kali. Umur larva ikan ditentukan berdasarkan jumlah lingkaran pada otolit ditambah waktu terbentuknya lingkaran pertama kali se-jak penetasan. Waktu pemijahan larva ikan diduga dengan perhitungan balik dari waktu sampling ditambah umur dan masa pengeraman. Hasil penelitian menunjukkan sebanyak 130 juwana ikan red devil dengan kisaran panjang 7,0-14,6 mm berhasil dikumpulkan dan sebanyak 69 otolit berhasil diamati. Pembentukan lingkaran pada otolit nila albino dimu-lai pada hari ketujuh setelah pemijahan atau hari ketiga setelah penetasan dan terbentuk secara harian. Juwana ikan red devil berumur 9-28 hari, yang didominasi oleh larva berumur 17 hari. Ikan red devil memijah setiap bulan dari November hingga Februari, bertepatan dengan bulan fase gelap dan curah hujan tinggi.